A kind of scratch-resistant polymer auxiliary agent and preparation method thereof
Through the use of a scratch -resistant polymer assistant with silicon dioxide, branches -like polymer modifiers, phenyl ethylene silicon oil, alkyl ethylene silicon oil, and lubricating coupling agent to solve The problem of stress -whitening in the process of scraping by polymer materials, significantly improved the scratch resistance and appearance quality of the material.
Patent Information
- Application Number
- CN202111438621.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-29
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-11-29
AI Technical Summary
Existing polymer materials are prone to stress whitening during scratching, resulting in uneven appearance of the product and affecting quality.
The use of a scratch -resistant polymer additive, which includes silicon dioxide, branches -like polymer modifiers, phenyl ethylene silicon oil, alkyl ethylene silicon oil and lubricant puppet co -modified agent. Through these components The complexity of the inorganic material and the compatibility and interface binding force of the high molecular substrate will be improved, the friction coefficients will be reduced, and the surface light and smoothness and smoothness will be improved.
Effectively improve the scratch resistance of thermoplastic elastic material, avoid the white phenomenon caused by interface damage during scratching, and significantly improve the appearance quality of the material.
Smart Images

Figure BDA0003379961280000051 
Figure BDA0003379961280000061 
Figure BDA0003379961280000062
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic processing, and in particular to a scratch-resistant polymer additive and a preparation method thereof. Background Art
[0002] Polymer additives, also known as plastic additives, are some compounds that must be added to polymer materials during molding to improve their processing properties or to improve the insufficient properties of the resin itself. For example, plasticizers are added to reduce the molding temperature of polyvinyl chloride resin and make the product soft; foaming agents are added to prepare lightweight, vibration-resistant, heat-insulating, and sound-insulating foam plastics; the thermal decomposition temperature of some plastics is very close to the molding temperature, and they cannot be molded without the addition of heat stabilizers. Therefore, plastic additives occupy a particularly important position in plastic molding.
[0003] According to the role and function of plastic additives, polymer additives can be divided into lubricants, mold release agents, stabilizers, flame retardants, plasticizers, reinforcing agents and foaming agents. Lubricants can reduce the friction between resin particles, resin melt and processing equipment, and between molecules in the resin melt, and improve its fluidity and demolding properties during molding. They are processing modification additives and are mostly used in the processing and molding of thermoplastics, including hydrocarbons (such as polyethylene wax, paraffin, etc.), fatty acids, fatty alcohols, fatty acid soaps, fatty acid esters and fatty amides. Mold release agents can be applied to the surface of molds or processing machinery, or added to base resins to make molded products easy to demold.
[0004] In order to reduce costs and improve the dimensional stability and rigidity of materials, the prior art often uses the method of adding inorganic material components to polymer materials, such as calcium carbonate, talcum powder, barium sulfate, glass fiber and other components. However, inorganic materials have poor compatibility with polymer matrices and weak interface bonding force. Microcracks are easily generated under stress when scratched, and the microcracks expand to form silver streaks, and the appearance appears white, that is, stress whitening. This phenomenon is more likely to occur when bending or scratching. The stress-whitened part is prone to uneven color, and there are problems with product quality. Therefore, how to solve the stress whitening problem under scratching is an unavoidable problem in the processing and application of polymer materials. Existing amide lubricants, slip agents and other components migrate to the surface of the material and reduce the whitening problem by reducing the friction coefficient, but they have a greater impact on printing and surface adhesion. For example, because thermoplastic elastomer materials are relatively soft and the polymer chain segments have strong mobility, the above-mentioned additives are easy to migrate at room temperature, resulting in surface stickiness or spraying, affecting the performance and subsequent processing performance. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a scratch-resistant polymer additive and a preparation method thereof. The scratch-resistant polymer additive is suitable for thermoplastic elastomer materials, can prevent the surface of the material from whitening, and improve the scratch resistance.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] In a first aspect, the present invention provides a scratch-resistant polymer additive, comprising the following components by weight: 20 to 30 parts of silicon dioxide, 15 to 50 parts of a dendritic polymer modifier, 10 to 20 parts of phenyl vinyl silicone oil, 10 to 20 parts of an alkyl vinyl silicone oil, and 5 to 15 parts of a lubricating coupling modifier. The lubricating coupling modifier comprises a glycidyl methacrylate functional group.
[0008] The lubricating coupling modifier of the present invention contains a glycidyl methacrylate functional group, which can realize the anchoring of a polymer matrix and an inorganic material. One end of the structure is adsorbed on the surface of the inorganic material, and the other end is entangled with the chain segments of the polymer matrix, thereby generating a good volume expansion effect, improving the compatibility between the inorganic material and the polymer matrix, and increasing the interfacial force between the two phases. By compounding with a dendritic polymer modifier, an alkyl vinyl silicone oil, and a phenyl vinyl silicone oil, the precipitation problem caused by excessive addition of a single component is avoided, the rheological properties and the surface defects of the thermoplastic elastomer prepared by the scratch-resistant polymer additive are improved, the surface friction coefficient is reduced, and the brightness and smoothness of the surface layer of the thermoplastic elastomer are increased, thereby achieving a good scratch-resistant modification effect.
[0009] As a preferred embodiment of the scratch-resistant polymer additive of the present invention, the specific surface area of the silicon dioxide is 145 to 170 m 2 / g.
[0010] As a preferred embodiment of the scratch-resistant polymer additive of the present invention, the viscosity of the phenyl vinyl silicone oil is 2000-3000 cps.
[0011] As a preferred embodiment of the scratch-resistant polymer additive of the present invention, the viscosity of the alkyl vinyl silicone oil is 10000-13000 cps.
[0012] As a preferred embodiment of the scratch-resistant polymer additive of the present invention, the brand of the dendritic polymer modifier is CYD-P214, produced by Weihai Chenyuan Polymer Materials Co., Ltd. The product is synthesized by repeated growth reaction, is highly branched, and the thermoplastic elastomer prepared by the scratch-resistant polymer additive containing CYD-P214 has low melt viscosity, good rheological properties and no surface defects, which effectively improves the brightness and smoothness of the surface of the thermoplastic elastomer.
[0013] In a second aspect, the present invention provides a method for preparing the scratch-resistant polymer additive, comprising the following steps:
[0014] According to the weight ratio, weigh each component, mix and stir evenly, and discharge the material to obtain the product.
[0015] In a third aspect, the present invention provides a thermoplastic elastomer comprising the following components, by weight: 15-25 parts of SEBS, 15-20 parts of polypropylene, 35-45 parts of paraffin oil, 15-25 parts of calcium carbonate, 0.1-0.2 parts of antioxidant, and 2-4 parts of the polymer additive.
[0016] In a fourth aspect, the present invention provides a method for preparing the thermoplastic elastomer, comprising the following steps:
[0017] (1) mixing the SEBS and paraffin oil to obtain an oil-extended mixture;
[0018] (2) preheating the calcium carbonate, adding the polymer additive and stirring, then adding the polypropylene and antioxidant and mixing; adding the oil-filled mixture and stirring to obtain a premix;
[0019] (3) Extruding and granulating the obtained premix.
[0020] As a preferred embodiment of the method for preparing a thermoplastic elastomer of the present invention, during the extrusion, the temperatures in each zone are controlled as follows: zone one temperature 160±10°C, zone two temperature 170±10°C, zone three temperature 180±10°C, zone four temperature 180±10°C, zone five temperature 180±10°C, zone six temperature 180±10°C, zone seven temperature 180±10°C, zone eight temperature 180±10°C, zone nine temperature 180±10°C.
[0021] In a fifth aspect, the present invention applies the scratch-resistant polymer additive or thermoplastic elastomer to daily or office supplies, auto parts, household appliances and electric tools.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The scratch-resistant polymer additive of the present invention can effectively improve the scratch resistance of thermoplastic elastomer materials, avoid the whitening phenomenon caused by interface damage during the scratching process, and has broad application prospects in the fields of daily necessities, household appliances, power tools, etc. DETAILED DESCRIPTION
[0024] To better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be understood by those skilled in the art that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0025] Unless otherwise specified, the experimental methods used in the examples are all conventional methods; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial channels.
[0026] The raw materials used in the following examples and comparative examples are described as follows, but are not limited to these materials:
[0027] Dendritic polymer modifier, brand name CYD-P214, Weihai Chenyuan Polymer Materials Co., Ltd.;
[0028] Silicon dioxide 1, brand name HM-1160, specific surface area 145~170m 2 / g, produced by Jiangxi Black Cat Carbon Black Co., Ltd.;
[0029] Silicon dioxide 2, brand name HM-1170, specific surface area 165~190m 2 / g, produced by Jiangxi Black Cat Carbon Black Co., Ltd.;
[0030] Silicon dioxide 3, brand name HM-1180, specific surface area 170~200m 2 / g, produced by Jiangxi Black Cat Carbon Black Co., Ltd.;
[0031] Phenyl vinyl silicone oil 1, viscosity 2000cps, Guangzhou Silicon Carbon New Materials Co., Ltd.;
[0032] Phenyl vinyl silicone oil 2, viscosity 3000cps, Guangzhou Silicon Carbon New Materials Co., Ltd.;
[0033] Phenyl vinyl silicone oil 3, viscosity 1000cps, Guangzhou Silicon Carbon New Materials Co., Ltd.;
[0034] Phenyl vinyl silicone oil 4, viscosity 4000cps, Guangzhou Silicon Carbon New Materials Co., Ltd.;
[0035] Alkyl vinyl silicone oil 1, viscosity 10000cps, Guangzhou Silicon Carbon New Materials Co., Ltd.;
[0036] Alkyl vinyl silicone oil 2, viscosity 13000cps, Dow Corning;
[0037] Alkyl vinyl silicone oil 3, viscosity 15000cps, Dow Corning;
[0038] Alkyl vinyl silicone oil 4, viscosity 8000cps, Dow Corning;
[0039] Lubricating coupling modifier, brand name YY-503, produced by Guangzhou Yuantai Synthetic Materials Co., Ltd.; contains glycidyl methacrylate (GMA) functional group structure;
[0040] SEBS elastomer material, brand name SEBS 6154, Formosa Plastics Corporation;
[0041] Polypropylene, brand HP550J, from CNOOC and Shell;
[0042] Paraffin oil, commercially available;
[0043] Calcium carbonate, commercially available;
[0044] Antioxidant 1010 and Antioxidant 168, commercially available;
[0045] Lubricant: ethylene bis( ...
[0046] In the following embodiments and comparative examples, the performance testing method is:
[0047] (1) Melt index
[0048] The test was carried out in accordance with GB / T 3682-2000 Determination of mass flow rate and volume flow rate of thermoplastic melts, with a temperature of 190°C and a load of 5 kg.
[0049] (2) Hardness
[0050] The test was conducted using a Shore A hardness tester according to ISO 868:2003 Plastics and hard rubber - Determination of indentation hardness (Shore hardness) using a hardness tester, with a delay time of 15 seconds.
[0051] (3) Tensile strength and elongation at break
[0052] The test was carried out in accordance with ISO 37-2007 Rubber, vulcanized or thermoplastic. Determination of tensile stress-strain properties, and the tensile rate was 500 mm / min.
[0053] (4) Scratch resistance
[0054] According to the cross scratch method of "GMW14688 (General Standard: Scratch Resistance Test Method)", 1% of the above materials are added to the black masterbatch injection molding standard sample, the scratching force is 5N, and the color change △L* value of the scratch before and after scratching is tested by a colorimeter to evaluate the scratch resistance. The smaller the color difference, the better the scratch resistance of the material.
[0055] (5) Surface precipitation evaluation
[0056] The injection molded color plate was aged in an oven at 60°C for 168 hours, and then placed at room temperature for 168 hours to observe and evaluate whether the surface was sticky or frosted.
[0057] Embodiment and comparative example:
[0058] 1. Preparation of polymer additives
[0059] According to the weight ratio in Table 1, weigh each component in proportion, add it into the stirrer, start the stirrer and control the speed to 200-500rpm, stir it thoroughly and then discharge the material to obtain the polymer additive.
[0060] Table 1 Proportions of the components of the polymer additives in the examples and comparative examples
[0061]
[0062]
[0063] 2. Preparation of Thermoplastic Elastomer
[0064] Thermoplastic elastomers include the following components by weight:
[0065] SEBS 615420 parts, polypropylene 16.8 parts, paraffin oil 40 parts, calcium carbonate 20 parts, antioxidant 10100.1 parts, antioxidant 1680.1 parts, polymer additive 3 parts.
[0066] The specific preparation method of the thermoplastic elastomer is as follows:
[0067] First, SEBS and paraffin oil are mixed and filled with oil, and then placed for 24 hours for use; calcium carbonate is preheated and mixed in a high-speed mixer at a temperature of 140°C for 5 minutes, and then a scratch-resistant polymer additive is added and stirred at high speed for 10 to 15 minutes for surface treatment, and then polypropylene, antioxidant 1010, and antioxidant 168 are added and mixed evenly, and finally a mixture of SEBS and paraffin oil is added and stirred for 2 to 3 minutes to obtain a premix.
[0068] The premix is melt-mixed and extruded into granules by a twin-screw extruder to obtain the product;
[0069] Among them, the temperatures of the heating zone of the twin-screw extruder from the feeding port to the die head are set to 160°C, 170°C, 180°C, 180°C, 180°C, 180°C, 180°C, 180°C, and the rotation speed is 300rpm.
[0070] The thermoplastic elastomer materials prepared in Examples 1 to 5 and Comparative Examples 1 to 11 were injection molded into standard mechanical specimens and color plates at 200° C. using an injection molding machine, and cylindrical hardness sheets were pressed under the conditions of preheating for 6 minutes, hot pressing for 1 minute, and cooling for 5 minutes at 210° C. The performance test was carried out after being placed at room temperature for 24 hours. The test results are shown in Table 2.
[0071] The performance test results of the thermoplastic elastomers obtained in the examples and comparative examples are shown in Table 2.
[0072] Table 2 Proportions of the thermoplastic elastomer components in the examples and comparative examples
[0073]
[0074] Table 2 Proportions of the thermoplastic elastomer components in the examples and comparative examples
[0075]
[0076] From the performance data in Table 2, we can see that:
[0077] The thermoplastic elastomers prepared by the polymer additives of Examples 1 to 5 have relatively high MFR, improved flow properties, high tensile strength and elongation at break, and small color difference values, especially the color difference values of Examples 3 to 5 are less than 0.9, and no obvious color difference can be observed with the naked eye, indicating that the thermoplastic elastomers prepared by the polymer additives of Examples 1 to 5 have a good scratch resistance effect on the basis of ensuring the mechanical properties of the material.
[0078] The thermoplastic elastomers prepared by the polymer additives of Example 1 and Comparative Example 1, when no silicon dioxide is added to the polymer additives, have reduced tensile strength and a color difference of 0.97, which is obvious to the naked eye.
[0079] The thermoplastic elastomer prepared by the polymer additives of Example 1 and Comparative Examples 2 and 3 has a specific surface area of 165 to 190 m 2 / g and fineness is 170~200m 2 / g of silica, compared with the polymer additive in Example 1, which has a specific surface area of 145 to 170 m 2 / g of silica, although the hardness is not much different, the flowability is relatively reduced, and the color difference is 0.98 and 0.99, which can be observed with the naked eye.
[0080] The thermoplastic elastomer prepared by the polymer additives of Example 2 and Comparative Example 4, when no dendritic polymer modifier is added to the polymer additives, has reduced flow properties, reduced tensile strength and elongation at break, and a color difference value of 1.2, which is obvious to the naked eye.
[0081] The thermoplastic elastomer prepared by the polymer additives of Example 3 and Comparative Example 5, when no phenyl vinyl silicone oil was added to the polymer additives, had a color difference value of 0.92, and the additives precipitated from the material, resulting in a sticky phenomenon.
[0082] When phenyl vinyl silicone oil with a viscosity of 1000cps or 4000cps was added to the thermoplastic elastomer prepared by the polymer additives of Example 3 and Comparative Examples 6 and 7, respectively, compared with the phenyl vinyl silicone oil with a viscosity of 3000cps in the polymer additive of Example 1, the polymer additive of Comparative Example 6 precipitated from the material and became sticky and frosted; the color difference of the polymer additive of Comparative Example 7 was 1.2, and obvious color difference could be observed with the naked eye.
[0083] The thermoplastic elastomer prepared by the polymer additives of Example 4 and Comparative Example 8, when no alkyl vinyl silicone oil is added to the polymer additives, has a color difference value of 1.0, and obvious color difference can be observed with the naked eye. In addition, the additives precipitate from the material, resulting in stickiness.
[0084] When the thermoplastic elastomers prepared by the polymer additives of Example 4 and Comparative Examples 9 and 10 respectively add alkyl vinyl silicone oil with a viscosity of 15000cps or a viscosity of 8000cps to the polymer additives, compared with the alkyl vinyl silicone oil with a viscosity of 13000cps in the polymer additive of Example 4, the color difference of the polymer additive of Comparative Example 9 is 1.24, the color difference value increases, and the color difference is obviously observable to the naked eye; the polymer additive of Comparative Example 10 precipitates from the material and becomes sticky.
[0085] The thermoplastic elastomer prepared by the polymer additives of Example 5 and Comparative Example 11 has relatively reduced flow properties when no lubricating coupling modifier is added to the polymer additives, with a color difference of 1.23, which is obvious to the naked eye, and the additives precipitate from the material, resulting in stickiness and frosting.
[0086] For the thermoplastic elastomer prepared by the polymer additives of Example 4 and Comparative Example 12, when the lubricating coupling modifier in the polymer additive is replaced with ethylene bis(vinyl chloride) amide, the flow properties are reduced, the tensile strength and the elongation at break are reduced, and the color difference value is 1.45. The obvious color difference can be observed with the naked eye, and the additive precipitates from the material, causing stickiness and frosting.
[0087] For the thermoplastic elastomers prepared with the polymer additives of Example 5 and Comparative Example 13, when the lubricating coupling modifier in the polymer additive is replaced with erucamide, the flow properties are reduced, the tensile strength and the elongation at break are reduced, and the color difference value is 1.32, and the obvious color difference can be observed with the naked eye. In addition, the additive precipitates from the material, causing stickiness and frosting.
[0088] The thermoplastic elastomers prepared by the polymer additives of Examples 1 to 5 and Comparative Examples 14 and 15 show that the thermoplastic elastomer of Comparative Example 14 has reduced flow properties, and reduced tensile strength and elongation at break; the thermoplastic elastomer of Comparative Example 15 has good mechanical properties, but its color difference value is 1.26, and obvious color difference can be observed with the naked eye, and the additives are precipitated from the material, resulting in stickiness and frosting.
[0089] In summary, adding the polymer additives of Examples 1 to 5 to thermoplastic elastomer materials has good mechanical properties, no precipitation phenomenon, and excellent scratch resistance, and has good application prospects in the fields of daily necessities, office automation, auto parts, home appliances, and power tools.
[0090] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A scratch-resistant polymer additive, characterized in that: The composition comprises the following components by weight: 20 to 30 parts of silicon dioxide, 15 to 50 parts of dendritic polymer modifier, 10 to 20 parts of phenyl vinyl silicone oil, 10 to 20 parts of alkyl vinyl silicone oil, and 5 to 15 parts of lubricating coupling modifier; The lubricating coupling modifier comprises a glycidyl methacrylate functional group; The specific surface area of the silicon dioxide is 145 to 170 m 2 / g; The viscosity of the phenyl vinyl silicone oil is 2000-3000cps; The viscosity of the alkyl vinyl silicone oil is 10000-13000 cps; The brand of the dendritic polymer modifier is CYD-P214, produced by Weihai Chenyuan Polymer Materials Co., Ltd.
2. The method for preparing the scratch-resistant polymer additive according to claim 1, characterized in that: The following steps are involved: According to the weight ratio, weigh each component, mix and stir evenly, and discharge the material to obtain the product.
3. A thermoplastic elastomer, characterized in that The invention comprises the following components by weight: 15-25 parts of SEBS, 15-20 parts of polypropylene, 35-45 parts of paraffin oil, 15-25 parts of calcium carbonate, 0.1-0.2 parts of antioxidant and 2-4 parts of the scratch-resistant polymer additive according to claim 1.
4. The method for preparing the thermoplastic elastomer according to claim 3, characterized in that: The following steps are involved: (1) mixing the SEBS and paraffin oil to obtain an oil-extended mixture; (2) preheating the calcium carbonate, adding the scratch-resistant polymer additive and stirring, then adding the polypropylene and antioxidant and mixing; adding the oil-filled mixture and stirring to obtain a premix; (3) Extruding and granulating the obtained premix.
5. The method for preparing a thermoplastic elastomer according to claim 4, characterized in that: During the extrusion, the temperatures in each zone are controlled as follows: zone one at 160±10°C, zone two at 170±10°C, zone three at 180±10°C, zone four at 180±10°C, zone five at 180±10°C, zone six at 180±10°C, zone seven at 180±10°C, zone eight at 180±10°C, and zone nine at 180±10°C.
6. Use of the scratch-resistant polymer additive according to claim 1 in daily or office supplies, auto parts, household appliances and electric tools.
7. Use of the thermoplastic elastomer according to claim 3 in daily or office supplies, automobile accessories, household appliances and electric tools.
Citation Information
Patent Citations
Quick-drying, energy-elastic, scratch-resistant and stable coating compounds
CN106459345A
Low-odor sterilization reinforced ABS (acrylonitrile butadiene styrene) automobile rearview mirror frame material and method for preparing same
CN107915948A